2020
DOI: 10.1155/2020/4248029
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile SERS Sensor for Multiple Determinations of Polycyclic Aromatic Hydrocarbons and Its Application Potential in Analysis of Fried Foods

Abstract: Polycyclic aromatic hydrocarbons (PAHs), due to their high hydrophobicity, have low affinity for metallic SERS-active surfaces, which leads to their low SERS detection sensitivity. Various functional groups have been used to improve the affinity of metallic substrates towards the target PAHs. However, a large portion of the signals generated from the “first-layer effect” of the functionalized substrates may complicate the spectrum, leading to a distortion in the assignment of the intrinsic SERS fingerprints of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, few of them were applied in real food samples. Wang et al (2020) developed a surface-enhanced Raman scattering sensor for simultaneous detection of 16 PAHs in fried foods within 15 min, showing the potential of onsite screening of PAHs in food samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few of them were applied in real food samples. Wang et al (2020) developed a surface-enhanced Raman scattering sensor for simultaneous detection of 16 PAHs in fried foods within 15 min, showing the potential of onsite screening of PAHs in food samples.…”
Section: Methodsmentioning
confidence: 99%
“…Supercritical fluid extraction is able to extract PAHs selectively and efficiently from complex matrices under the supercritical condition; however, the final solvent evaporation step may cause loss or degradation of the analytes (Kayali‐Sayadi, Rubio‐Barroso, García‐Iranzo, & Polo‐Díez, 2000; Ali & Cole, 2001; Amezcua‐Allieri, Ávila‐Chávez, Trejo, & Meléndez‐Estrada, 2012). Other cutting‐edge techniques that consume lower amounts of solvent and reduce experimental steps have been reported, such as matrix‐solid phase dispersion (Pensado, Casais, Mejuto, & Cela, 2005; Olson, Meyer, & Portier, 2014), membrane‐assisted solvent extraction (Rodil, Schellin, & Popp, 2007), microwave‐assisted extraction (Germán‐Hernández, Pino, Anderson, & Afonso, 2012), ultrasound‐assisted solvent extraction (Veiga et al., 2014), ultrasound‐assisted emulsification‐microextraction (USAEME) (Yebra‐Pimentel, Martínez‐Carballo, Regueiro, & Simal‐Gándara, 2013), stir‐bar sorptive extraction (SBSE) (Kolahgar, Hoffmann, & Heiden, 2002), solid‐phase micro‐extraction (SPME) (King, Readman, & Zhou, 2004; Purcaro, Moret, & Conte, 2007; Purcaro, Morrison, Moret, Conte, & Marriott, 2007; Lin, Wei, Jiang, Zhu, & Ouyang, 2016; Jalili, Barkhordari, & Ghiasvand, 2020), magnetic solid‐phase extraction (MSPE) (Zhao et al., 2011; Zhang et al., 2017), dispersive liquid–liquid micro‐extraction (DLLME) (Rezaee et al., 2006; Cai, Stevens, & Syage, 2012; Kamankesh, Mohammadi, Hosseini, & Modarres Tehrani, 2015), and the quick, easy, cheap, rugged, effective, and safe (QuEChERS) method (Ramalhosa, Paíga, Morais, Delerue‐Matos, & Oliveira, 2009; Smoker, Tran, & Smith, 2010; Gratz et al., 2011; Kao, Chen, Chen, Huang, & Chen, 2012; El Husseini, Makkouk, Rabaa, Al Omar, & Jaber, 2018; Wang, Cheng, Han, & Xie, 2020). SPME is a solvent‐free single‐step pretreatment method with low detection limits and good performance, which is a favorable pretreatment technique for PAH analysis.…”
Section: Methods For Analyzing Pahs In Foodmentioning
confidence: 99%
“…In an attempt to develop a SERS method for simultaneous determination of 3 PAHs including PYR, ANT and PHE, Wang et al [ 108 ] prepared hybrid AgNPs decorated graphene as SERS substrate and reported a linear response in the concentration ranging from 0.02–2.02 × 10 4 μg/L for PYR and 0.02–1.78 × 10 4 μg/ L for both PHE and ANT, with the LOD at 0.73, 0.57 and 1.10 μg/L, respectively. In another study, a versatile SERS sensor with AuNPs decorated on doubly-oxidized graphene oxide was developed for simultaneous analysis of 16 EPA priority PAHs [ 109 ]. The typical peaks for all the 16 PAHs were identified in the SERS spectra of both standard mixture and Chinese traditional fried food (youtiao) with a LOD value ranging from 0.2 to 2.0 ng/mL, while the latter showed no significant background interference.…”
Section: Sers Based Optical Sensors For Detection Of Pahsmentioning
confidence: 99%
“…Taken together, compared to electrochemical sensors, a high number of SERS-based optical sensors developed recently showed a multiplexing capability to simultaneously detect 2–16 PAHs. For analysis of 16 PAHs, the SERS sensor with AuNPs deposited on GO showed a lower LOD (0.2–2 μg/ L) [ 109 ] compared to that deposited on Fe 3 O 4 nanoparticles (1.01–16.62 μg/L) [ 99 ]. Among the various SERS sensors with multiplexing capability of detecting 2–7 PAHs, the lowest LOD was shown for 7 PAHs (0.01–0.14 μg/L) with SERS-active colloidal AuNPs/NaCl [ 94 ], followed by 4 PAHs (0.04–0.15 μg/L) with porous copolymer-based colloid AuNPs [ 105 ], 3 PAHs (0.03–3.56 μg/L) with MOFs-based AgNPs [ 107 ] and 2 PAHs (0.08–0.78 μg/L) with β-cyclodextrin-based AuNPs [ 102 ].…”
Section: Sers Based Optical Sensors For Detection Of Pahsmentioning
confidence: 99%
“…The surfaces are generally modified by adding groups such as thiols, alkyl chains, antibodies, or -cyclodextrin ( -CD). Other strategies are based on the immobilization of PAH molecules on graphene-based supporters, to which plasmonic nanoparticles are then added [ 24 , 25 ]. As a matter of fact, PAHs do not contain any functional groups (except in the case of derivates) that could favor the metal–adsorbate bonding; hence, the chemical enhancement with SERS [ 26 ].…”
Section: Introductionmentioning
confidence: 99%